Applying the Kaizen in Africa A New Avenue for Industrial Development (Springer International Publishing, 2018)
At present, how to develop industries is a burning issue in Africa, where population growth remains high and economic development has thus far failed to provide sufficient jobs for many, especially young people and women. The creation of productive jobs through industrial development ought to be a central issue in steering economic activity across the continent. The authors of this book, consisting of two development economists and five practitioners, argue that the adoption of Kaizen management practices, which originated in Japan and have become widely used by manufacturers in advanced and emerging economies, is decisively the most effective first step for industrial development in Africa. This open access book discusses what Kaizen management is, why it is applicable to Africa, and why it can provide Africa with a springboard for sustainable economic growth and employment generation. Keijiro Otsuka is Professor at the Graduate School of Economics, Kobe University, Japan, and Chief Senior Researcher at the Institute of Developing Economies, Japan. Kimiaki Jin is Senior Assistant Director of the Industrial Development and Public Policy Department at the Japan International Cooperation Agency, Japan. Tetsushi Sonobe is Vice President and Chair of the PhD Program Committee, Director of the GRIPS Global Governance Program and Professor of Development Economics at the National Graduate Institute for Policy Studies (GRIPS), Japan.